Sea cucumbers and their symbiotic microbiome have evolved to feed on seabed sediments - Pan, Wenjie; Wang, Xuan; Ren, Chunhua; Jiang, Xiao; Gong, Sanqiang; Xie, Zhenyu; Wong, Nai-Kei; Li, Xiaomin; Huang, Jiasheng; Fan, Dingding; Luo, Peng; Yang, Yun; et al. (Nature communications, 2024)
Sea cucumbers are predominant deposit feeders in benthic ecosystems, providing protective benefits to coral reefs by reducing disease prevalence. However, how they receive sufficient nutrition from seabed sediments remains poorly understood. Here, we investigate Holothuria leucospilota , an ecologically significant tropical sea cucumber, to elucidate digestive mechanisms underlying marine deposit-feeding. Genomic analysis reveals intriguing evolutionary adaptation characterized by an expansion of digestive carbohydrase genes and a contraction of digestive protease genes, suggesting specialization in digesting microalgae. Developmentally, two pivotal dietary shifts, namely, from endogenous nutrition to planktonic feeding, and from planktonic feeding to deposit feeding, induce changes in digestive tract enzyme profiles, with adults mainly expressing carbohydrases and lipases. A nuanced symbiotic relationship exists between gut microbiota and the host, namely, specific resident bacteria supply crucial enzymes for food digestion, while other bacteria are digested and provide assimilable nutrients. Our study further identifies Holothuroidea lineage-specific lysozymes that are restrictedly expressed in the intestines to support bacterial digestion. Overall, this work advances our knowledge of the evolutionary innovations in the sea cucumber digestive system which enable them to efficiently utilize nutrients from seabed sediments and promote food recycling within marine ecosystems. Sea cucumbers are predominant deposit feeders in benthic ecosystems. This study elucidates the mechanisms within the sea cucumber digestive system and their symbiotic microbiome which enable them to efficiently utilize nutrients from seabed sediments.